PLK1 inhibition impairs erythroid differentiation - Jia, Peijun; Li, Yan; Duan, Lulu; Zhang, Jingxin; Xu, Yuanlin; Zhang, Huan; Wang, Chenghui; Gong, Yaqian; Zhang, Ying; Zhao, Longzhen; Huang, Yumin; Zhang, Shijie (Frontiers in Cell and Developmental Biology, 2024)
Polo-like kinase 1 (PLK1), a key regulator of the G2/M phase in mitosis, is frequently overexpressed in numerous tumors. Although PLK1 inhibitors have emerged as promising therapeutic agents for cancer, their use has been linked to significant anemia in a subset of patients, yet the underlying mechanisms remain poorly understood. In this study, we utilized an in vitro human umbilical cord blood-derived CD34+ cell-based erythroid differentiation system, alongside a murine model, to investigate the impact of PLK1 inhibitors on erythropoiesis. Our results indicate that PLK1 inhibitors, specifically GSK461364 and BI6727, significantly suppress the proliferation of erythroid cells, resulting in G2/M phase cell cycle arrest, increased apoptosis in erythroid cells, and the formation of abnormally nucleated late-stage erythroblasts. In vivo, administration of PLK1 inhibitors in mice induced severe anemia, as evidenced by a marked reduction in red blood cells and hemoglobin levels. More specifically, PLK1 inhibition impaired the differentiation and erythroid commitment of hematopoietic stem cells in the bone marrow, resulting in abnormal accumulation of BFU-E cells and reduced proliferation and differentiation of CFU-E, and a decrease in the number of terminal erythrocytes. Mechanistically, PLK1 inhibitors primarily induce apoptosis in erythroid cells by reducing Mitochondrial membrane potential and arresting the cell cycle at the G2/M phase. Overall, our findings underscore the critical role of PLK1 in erythropoiesis and shed light on the mechanisms underlying PLK1 inhibitor-induced anemia, providing essential guidance for developing strategies to prevent and manage anemia in clinical applications of PLK1-targeted therapies.